Contemplation and the University: Reflections on Liberal Education in the Age of Practice - Kinzel, Till (Horyzonty Polityki, 2011)
The article deals with the change that has occurred in the field of university education. The old notion of „contemplation” was thus thoroughly neglected, or „theory” reduced to „practice”, in order to redeem the claims of modern „technological” society. This society is built on the „imperatives of making and doing”. There is almost no learning for its own sake nowadays and we can find a fatal indifference to the real „message” of „the matters”, as distinguished from the „media” or „communicative competence”, as well. The humanities, however, should not be permeated by these currents; it should offer, instead, some alternative approach to education. Such approach may be linked with reflection on the figure of Socrates, who is not only a „historical philosopher”, but „a model for contemplation”. He was wholly immersed in the „practice of contemplation” yet he never forgot „the question of morality and politics”. We are not expected to take after historical Socrates; what we should do is to learn from his fate, as Allan Bloom used to do, what love for truth in reality means; we should actualize „Socratic impulse” while not imitating Socrates himself. We must be aware that the great philosophers would not probably be welcome in the realm of the „hypermodern bureaucratized university”; we do, nonetheless, have to reflect on their examples. This is primarily because contemplation leads to happiness. If there is no place for happiness, or reflecting upon happiness, as the ultimate goal of human life, at the university, the fundamental aim of education is decidedly diminished. But contemplation has also its political dimension and ought to be considered in regard to its „important educational function”, namely, teaching philosophy. After all, university professors are citizens, too. And political philosophy, if properly understood, shows the right distance but discourages men from „complete withdrawal from political action”. Contemplation can be seen as „an indicator of political and cultural freedom”. It should be present as a counterbalance of economic and political claims dominating our society. Artykuł dotyczy zmiany, jaka uwidoczniła się w domenie kształcenia uniwersyteckiego. Otóż całkowicie porzucono dawną ideę „kontemplacji” – „teoria” została zredukowana do „praktyki” – po to, aby sprostać wymogom nowoczesnego społeczeństwa „technologicznego”. Społeczeństwo to zbudowane jest w oparciu o „imperatywy tworzenia i działania”. Współcześnie niemal nikt nie uczy się dla samej nauki, możemy tez stwierdzić fatalne zobojętnienie wobec przekazu dotyczącego prawdziwych znaczeń, nie zaś jedynie przekazu „środków przekazu” czy „umiejętności komunikowania”. Wszakże tego rodzaju prądy nie powinny wdzierać się do humianistyki; właśnie stąd powinno z kolei wypływać alternatywne podejście do edukacji. Takie podejście może łączyć się z refleksją na temat postaci Sokratesa, jako nie tylko postaci „historycznego filozofa”, lecz także jako „wzorca dla kontemplacji”. BYł on całkowicie zanurzony w „praktyce kontemplacji”, wszakże nigdy nie zapominał „pytania o moralność i politykę”. Nie chodzi o to, byśmy upodobniali się do Sokratesa historycznego; powiniśmy raczej uczyć się przez to, co go spotkało – jak czynił to Allan Bloom – co naprawdę znaczy umiłowanie prawdy; powiniśmy aktualizować w sobie „impuls Sokratejski”, nie naśladując przy tym samego Sokratesa. Miejmy świadomość tego, iż „hipernowoczesny, biurokratyczny uniwersytet” nie przyjąłby z otwartymi ramionami wielkich filozofów; niemniej jednak, musimy zastanawiać się nad ich przykładami. Przede wszystkim dlatego, że kontemplacja wiedzie do szczęścia. Jeśli w uniwersytecie nie ma miejsca na szczęście czy też namysł nad szczęściem, jako ostatecznym celem życia ludzkiego, to zasadniczo osłabia się fundamentalny cel kształcenia. Ale kontemplacja ma także wymiar polityczny i należy myśleć o niej, mając na względzie „ważną funkcję edukacyjną”, jaką jest nauka filozofii. Uniwersyteccy profesorowie też są przecież obywatelami. Zaś właściwie rozumiana filozofia polityczna, choć zarysowuje konieczny dystans, odwodzi od „całkowitego wycofania się z działania politycznego”. Kontemplacja może być postrzegana jako „wskaźnik wolności politycznej i kulturalnej”. Powinna ona stanowić przeciwwagę dla wymogów ekonomicznych i politycznych, jakie zdominowały nasze społeczeństwo.